The safety and feasibility of intraoperative near‐infrared fluorescence imaging with indocyanine green in thoracoscopic sympathectomy for primary palmar hyperhidrosis - Pei, Guotian (Thorac Cancer, 2020)
BACKGROUND: We investigated the safety and feasibility of intraoperative near‐infrared (NIR) imaging using indocyanine green (ICG) during sympathectomy in the management of primary palmar hyperhidrosis (PPH). METHODS: We performed a retrospective review of 142 patients (ICG group) who underwent endoscopic thoracic sympathectomy (ETS) between February 2018 and April 2019. All patients received a 5 mg/kg infusion of ICG 24 hours preoperatively. The vital signs before and after ICG injection and adverse reactions were recorded. Meanwhile, 498 patients (Non‐ICG group) who underwent ETS by normal thoracoscopy during August 2017 to April 2019 were also reviewed to compare the abnormal white blood cell (WBC) counts, alanine transaminase (ALT), aspartate transaminase (AST), blood urea nitrogen (BUN), and creatinine (Cr) levels before and after operation between two groups. RESULTS: For ICG group, the vital signs including body temperature, heart rate and blood pressure before and after ICG injection were stable. There was no significant difference in the abnormal WBC counts, ALT, AST, BUN, and Cr levels before and after operation between two groups. Only one patient had mild adverse reaction (0.7%) after ICG injection. The visibility rate of all sympathetic ganglions was 96.7% (1369/1415). The visibility rate from T1 to T5 was 98.23% (278/283), 98.23% (278/283), 97.17% (275/283), 95.76% (271/283), and 94.35% (267/283), respectively. There was no significant difference in the visibility rate with regard to age, gender, height, weight, body mass index, and PPH grade. CONCLUSIONS: NIR fluorescence imaging with ICG for identifying sympathetic ganglions is relatively safe and feasible. KEY POINTS: • Significant findings of the study. NIR fluorescence imaging with ICG for identifying sympathetic ganglions is relatively safe and feasible. • What this study adds. This technology may take the place of the rib‐oriented method as standard practice for the precise localization of sympathetic ganglions, and may improve the effect of sympathectomies.